Analysis of Factors Affecting Acceptance and Commitment Therapy (ACT) in Pulmonary TB Patients - Sri Mala Hayati; Jenny Marlindawani Purba; Cholina T. Siregar (Indonesian Journal of Global Health Research, 2022)
Pulmonary tuberculosis (TB) is a chronic infectious disease that is contagious and can cause death. Pulmonary TB is also a global health problem that causes the poor health of millions of people every year. Acceptance and Commitment Therapy (ACT) is one form of implementation to overcome client non-compliance with taking medication. The aim of this study was to analyze the factors that influence ACT in pulmonary TB patients. This study uses a descriptive research design with an analytical survey approach. The population is all pulmonary TB patients at the Frequent Health Center and the Glugur Health Center. The number of samples in this study amounted to 35 people. The sampling technique used is consecutive sampling. Analysis of the data used is the chi square test. The results showed that the results showed that there was a relationship between age and ACT (p value = 0.004., <0.005), there was no relationship between sex and ACT (p value = 0.006., <0.005), there was a relationship between length of time suffering from pulmonary TB. with ACT (p value= 0.001, <0.005), indicating that there is a relationship between age and ACT (p value= 0.001., <0.005) and there is a relationship between never getting counseling about pulmonary TB with ACT (p value= 0.004., <0.005). The conclusion of this study is that the factors that influence ACT in pulmonary TB patients are age, duration of suffering from pulmonary TB, length of time undergoing OAT treatment and having received health education about pulmonary TB.